Ventricular mechanics in adolescent and adult patients with a Fontan circulation: Relation to geometry and wall stress. - Rösner, Assami; Khalapyan, Tigran; Pedrosa, João; Dalen, Håvard; McElhinney, Doff B.; Friedberg, Mark K.; Lui, George K. (Echocardiography, 2018)
Background: Patients with single ventricle physiology and Fontan circulation are at increased risk for late complications and reduced survival. The aim of the study was to investigate the correlation between ventricular geometry and systolic regional function in different underlying anatomic conditions in adolescent and adult Fontan‐palliated patients. Method: In a retrospective cross‐sectional study, we measured 2D strain, ventricular diameters, ventricular volumes, ejection fraction (EF), global and segmental wall stress, and sphericity index. The same analyses were performed in 99 age‐ and gender‐matched healthy individuals. Results: One hundred and one patients were included at a mean age of 21 (range 14–59) years. In comparison with healthy subjects, patients with Fontan circulation displayed larger ventricular volumes (153 ± 78 mL vs 116 ± 38 mL P < 0.05), reduced EF (43% ± 15% vs 55% ± 8% P < 0.05), reduced longitudinal (−13% ± 6% vs −21% ± 4% P < 0.05) and circumferential strain values (−15% ± 7% vs −22% ± 4% P < 0.05). Functionally single ventricles were more spherical (ratio of longitudinal to short‐axis diameters 1.3 ± 0.3 vs 1.7 ± 0.2 P < 0.05). Circumferential strain correlated well with global wall stress and the degree of sphericity (R2 = 0.320), while segmental strain did not correlate with segmental wall stress. The percentage of segments with akinesia was relatively high (16 ± 16% vs 0 ± 0% P < 0.05) indicating reduced segmental contractile function. Conclusion: Functionally single ventricles after Fontan palliation have significantly reduced systolic regional and global function with a high intersegmental inhomogeneity. The underlying pathological mechanisms might be multifactorial, including ventricular geometry, sphericity, and regional contractile properties. Future studies are needed to investigate the role of ventricular geometry for clinical performance and outcome.